Early Effects of a ‘Train the Trainer’ Approach to Ponseti Method Dissemination: A Case Study of Sri Lanka - Jayawardena, Asitha (The University of Iowa, 2013)
BACKGROUND: The Ponseti method has been established as the standard of care for the treatment of clubfoot in many developed countries for its utility, cost-effectiveness, and efficiency. However, despite its being described as the gold-standard for clubfoot treatment, there are still many areas of the world bereft in formal training in the Ponseti method. This is especially important since 80% of patients with clubfoot are born in developing countries where the need is the greater for experienced providers. This study analyzes a ‘Train the Trainer’ approach, specifically in the island nation of SriLanka, as a model for future dissemination of the Ponseti method throughout the developing world. METHODS: A rapid ethnographic study design that included interviews, focus groups, and direct observation of 162 patients and healthcare practitioners directly involved with clubfoot care was conducted. RESULTS: The average age of the patients at the time of the interview was 75.4 weeks old (SD = 149.2), traveled 45.2 kilometers (SD = 49.8) to receive their care, and received 4 casts (SD = 2.2) for correction of the deformity. Since the initiation of the ‘Train the Trainer’ educational program, clubfoot clinics reportedly grew from 6-7 patients per week to over 60 patients per week. The majority of this patient population growth was attributed to word of mouth. Major barriers to the method included casting materials, bracing materials, and a lack of a dedicated area of the clinic to conduct tenotomies under local anesthesia. Of note, cost was not cited as a major barrier. CONCLUSION: Early evaluation suggests great utility of the ‘Train the Trainer’ method – especially regarding an increased patient demand for treatment. However, further studies are necessary to understand the long-term utility of this training methodology.